Hungarian Monitoring, 19 January 1989 . [Magyar rádiófigyelő], 1989. január 19 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Vienna follow-up talks conference comes to an end - Much more money need for reconstruction in Armenia than previously thought - Stormy Central Committee session in Warsaw - Prague criticizes foreign minister Schultz - Two important events in Yugoslavia - More demonstrations in Prague - Kohl reaction to Soviet missile disarmament proposal Domestic Affairs: - Ministerial council holds extraordinary session - First public meeting held by Hungarian Social Democratic Party - UNESCO international committee starts conference in Veszprém castle on links between top technology and science - Not one of the plans for the National Theater can be built - Hungarian Post Office accepts donations helping Hungarian refugees and Armenian earthquake injured for free Economy: - President of National Bank gives speech in European Parliament, says among other things that Hungary does not wish to be a member of the Common Market - South Korean firm Daewoo underwrites Hungarian bonds worth DM 2 million - French-Hungarian economic relations - No need for distributing land, self-governance of cooperatives should be allowed Külpolitika: - Befejeződött a bécsi utókonferencia: - Örményországban sokkal több pénz szükséges a helyreállításokhoz, mint ahogy azt előre tervezték - Viharos KB ülés Varsóban - Prága kritizálta Schultz külügyminisztert - Két fontos jugoszláviai esemény - Ismét tüntetések Prágában - Kohl reakció a szovjet rakéta leszerelési javaslatra Belpolitika: - Soron kívüli ülést tartott a Minisztertanács - Megtartotta első nyilvános ülését az MSZDP - Az UNESCO nemzetközi bizottsága a Veszprémi várban kezdett tanácskozást a csúcstechnológia és tudomány kapcsolatairól - A Nemzeti Színház díjazott pályaművei közül egyiket sem lehet megépíteni - A Magyar Posta ingyen fogadja el az erdélyi menekültek és az örményországi földrengés károsultjainak szánt adományokat Gazdaság: - A Nemzeti Bank elnöke az Európa Parlamentben tartott előadást, egyebek közt kifejtette, Magyarország nem kíván tagja lenni a Közös Piacnak - Magyar kötvényeket jegyez egy dél koreai cég a Daewoo 2 millió nyugatnémet márka értékben - Francia-magyar gazdasági kapcsolatok - Nincs szükség földosztásra, a szövetkezeteket önkormányzatát kell szabaddá tenni